ANALYSIS OF THE EFFECT OF SHOPAHOLIC BEHAVIOR AND PROMOTION ON IMPULSE BUYING THROUGH E-COMMERCE ON STUDENTS IN MEDAN - Daulay, Raihanah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Impulse buying is a condition where consumers feel interested in making purchases of the products they see. The conditions at that time where e-commerce became a trend for the development of shopaholic behavior and opportunities for impulse buying. Many factors can trigger impulse buying including shopaholic behavior and promotion. This study aims to determine the effect of shopaholic behavior and promotion which has an impact on impulse buying through e-commerce in the city of Medan. The sample of this research is students at private universities in Medan who like to shop at e-commerce in the last one year, the number of samples is 105 people. The data collection technique used a questionnaire that was tested for validity and reliability. The data analysis technique used assumption test, multiple linear regression, t test, F test and coefficient of determination. The results showed that shopaholic behavior had a significant effect on impulse buying and promotion had a significant effect on Impulse Buying. Simultaneously, shopaholic behavior and promotion affect Impulse Buying through e-commerce for students in Medan. Adjusted R Square of 67.2% shows the contribution of shopaholic behavior and promotion to impulse buying.